Practical aspects of initiation and use of SGLT2 inhibitors: inpatient and outpatient perspectives - V. V. Salukhov; G. R. Galstyan; T. A. Ilyinskay (Сахарный диабет)
In today`s therapy of type 2 diabetes mellitus, SGLT2 inhibitors have taken their rightful place both due to their positive hypoglycemic and outstanding cardiorenometabolic effects. Recent randomized clinical trials, such as DAPA HF, EMPEROR-Reduced and EMPEROR-Preserved, show the benefits of their use in the treatment of patients with chronic heart failure without regard to the status of type 2 diabetes mellitus and so significantly expands the range of use of SGLT2 in the practice of doctors of various specialties. This review presents not only the results of the most significant studies of SGLT2 inhibitors, but also the main approaches to the starting therapy with this class of drugs in various clinical situations, both inpatient and outpatient. In addition, potential adverse events and limitations associated with the use of SGLT2 inhibitors are discussed in detail, which must be taken into account when prescribing in particular patient. The practical aspects of SGLT2 inhibitors` prescription are considered separately through the prism of their safe use in the perioperative and postinfarction periods, as well as during other special conditions. Particular attention is paid to the monitoring of physical and general examination data and laboratory instrumental tests, the consideration of which will minimize adverse events and best benefit for many cardiological, endocrinological and nephrological patients.